The Effect of Price, Promotion and Product Quality on the Decision to Repurchase Liquid Fertilizer - Imma Nurhayati; Mohammad Yaskun; Evi Fitrotun Najiah (Jurnal Ekonomi, Akuntasi dan manajemen Indonesia (JEAMI), 2024)
This study aims to determine the effect of price, promotion, and product quality on the decision to repurchase liquid fertilizer. UD Primatan Mikro either partially, simultaneously and is the most dominant factor among the three variables above that influence repurchase decisions. This type of research is quantitative with a sample of 57 people. The sampling technique is Validity Test, Reliability Test, Classical Assumption Test, Multiple Correlation Analysis, Multiple Linear Regression Analysis, Coefficientof Determination Analysis, t Test, F Test. The results of this test result that the variables of Price, Promotion and Product quality partially influence the Buyer's Decision UD Primatan Mikro. The results show that the price (X1) = 3.012 < t table 2005, promotion (X2) = 2.466 < t table 2005, product quality (X3) = 2.605 < t table 2005. then H0 is rejected and Ha is accepted. F test evidence obtained Fcount = 28,817 > Ftable = 3.17 means that the independent variable simultaneously affects the dependent variable. 3. The results of calculations using Multiple Linear Regression Test obtained that the most dominant is Promotion (X1) with a regression coefficient value of 0.363 and a standard beta coefficient of 0.359, compared to the Product Quality variable (X3), the standard regression coefficient of 0.261 and the standard beta coefficient of 0.283 and price variable (X2) the standard regression coefficient is 0.358 and the standard beta coefficient is 0.323.7. The results of the hypothesis test show . Price, Promotion, and Product Quality have a significant positive positive impact in t table 2005 so that t count 3,014 > t table 2,005 and a significant value 0.004 < 0.05 then H0 is rejected and Ha is accepted, meaning that there is a partially significant effect between the price variables. (X1) against the buyer's decision (Y) UD. Primatan Mikro.